Innovation in Business Management Exploring the Path to Competitive Excellence - Delhi, Ariana; Sana, Eirene; Angelina Bisty, Alice; Husain, Abigail (APTISI Transactions on Management (ATM), 2024)
In the realm of business management, the focal point has shifted towards innovation as a pivotal endeavor for attaining a competitive edge. This study aims to delve into the repercussions of innovation in business management and accentuate its pivotal role in forging pathways to competitive advantage. The Structural Equation Modeling (SEM) analysis, employing the SmartPLS tool, was employed to scrutinize data gathered from 150 respondents representing Micro, Small, and Medium Enterprises (UMKM) in Indonesia across four distinct sectors: fashion, furniture, home decoration, and services. The analysis reveals a noteworthy impact of innovation on various facets of business management, encompassing strategy, organizational operations, and marketing. These findings underscore that organizations adept at integrating innovation into their management practices can cultivate sustainable competitive advantages. Furthermore, the research spotlights critical factors influencing the implementation of innovation, including leader support, organizational culture, and the ability to navigate risk. This study furnishes invaluable insights for practitioners and decision-makers by underscoring the significance of innovation in fortifying competitive positions. The practical implications of these findings suggest that MSMEs fostering a culture of innovation, backed by leadership support and adept risk management, stand poised to enhance their performance and competitiveness within the increasingly intricate and dynamic markets.